The Influence of Group Cohesivity and Working Discipline on the Performance Teachers of Private Senior high school In East Jakarta - Lisa Andriyati; Masduki Ahmad; Rochanah Rochanah (International Journal of Education, Information Technology, and Others, 2020)
This research aims to find out: (1) the effect of group cohesiveness toward performance; (2) the effect of work discipline toward performance; (3) the effect of group cohesiveness toward work discipline. This research uses survey method. Hypothesis testing with path analysis testing. The unit of analysis in this study is teacher on senior high school in East Jakarta with a sample of 199 people selected using random sampling techniques. The results showed that: (1) there is a direct positive effect of group cohesiveness toward performance; (2) there is a direct positive effect of work discipline toward performance; (3) there is a direct positive effect of group cohesiveness toward work discipline.